Microwave-assisted pilot-scale biodiesel production and engine tests - GÜL, MEHMET ZAFER (ICE PUBLISHING, 2019)
A pilot-scale microwave-assisted biodiesel reactor (60 I) was designed, manufactured and utilised to produce biodiesel from sunflower, canola and soybean oils. In addition, the engine performance and exhaust emissions of sunflower-based biodiesel and its blend with petroleum diesel (BO, B5, B10, B20 and B100) were tested using a single-cylinder, direct-injection diesel engine under constant speed and partial loads. The results carried out under microwave irradiation showed that 5 min transesterification in the presence of 1.0% potassium hydroxide and 6:1 methanolto-oil molar ratio was adequate for converting pilot scales of sunflower, canola and soybean oils to biodiesel having >95.95% ester yield, >96.5% ester content, 15-5 mm(2)/s kinematic viscosity and 0.860-0.900 g/cm(3) density values. The engine test data indicated that under experimental conditions, brake thermal efficiency, exhaust temperature and emissions of carbon monoxide and hydrocarbons were reduced with increase in concentration of biodiesel in the blend while emissions of nitrogen oxides and brake-specific fuel consumption were getting worse. As a result of this study, microwave technology could be adapted to a pilot-scale biodiesel batch reactor, and biodiesel suitable for use in diesel engines has been manufactured more efficiently and accomplished faster than conventional systems.
Keywords: energy; environment; pollution; ALKALI-CATALYZED TRANSESTERIFICATION; FUEL PROPERTIES; COMBUSTION CHARACTERISTICS; EMISSION CHARACTERISTICS; EXHAUST EMISSIONS; METHYL-ESTERS; VEGETABLE-OIL; DIESEL FUEL; PERFORMANCE; OPTIMIZATION